(untitled) (Agro Productividad, 2024)
Objective: To characterize the ways and magnitude in which herbal medicine mitigates health problems and represents a source of savings; as well as to identify the most common ailments treated with herbal medicine and the most used medicinal plants in Santiago Ixtaltepec, Nochixtlán, Oaxaca. Design/methodology/approach: The study was conducted in 2022, with a quantitative approach and a descriptive-correlational scope. Data were obtained through a survey, applied through direct interviews. Once the data were obtained in the field, they were systematized and processed in Excel databases and descriptive statistical analysis was performed to determine frequencies, percentages, means and other measures of dispersion. Results: The use of herbal medicine is relevant as an alternative in health care for the community’s population. The most common ailments treated with herbal medicine are stomach aches, postpartum treatment, cough, fever, and bad breath, and the most commonly used medicinal plants are coyote grass, horehound (Marrubium vulgare), cancer grass, puli (Pinaropappus roseus), and juniper (Juniperus deepeana). Limitations on study/implications: As this is a case study, the findings are not generalizable but specific to the community of study. Findings/conclusions: Herbal medicine contributes to the mitigation of health problems and its use has an impact on the economy of families. There is a direct relationship between the most common symptoms and the most used plants in the community.